1994
DOI: 10.4141/cjas94-035
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the effects of somatotropin and enhanced growth rate on the occurrence of osteochondrosis in pigs

Abstract: of iomatotropin and enhanced growth rate on the occurrence of osteochondrosis in pigs. Can. J. Anim' One hundred ind twenty yorkshiie pigs, equal numbers of gilts and barrows, with an initial average weight of 69 kg were us.ec in the present experiment. The animili weri treated with 2 -mg d -r of recombinant porcine somatotropin-(rpST). either b{ dqY injecti6n or by siow-release implant, while the control animals were treated with a sham implant. The daily injection of rpST increased daily weight gain (P j O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…These results confirm our previous observation (He et al 1994) that increased mechanical stress due to enhanced growth rate was not the only factor influencing the occurrence of OC in pigs.…”
Section: Methodssupporting
confidence: 82%
“…These results confirm our previous observation (He et al 1994) that increased mechanical stress due to enhanced growth rate was not the only factor influencing the occurrence of OC in pigs.…”
Section: Methodssupporting
confidence: 82%
“…Cartilage lesion score was marginally increased (P < 0.07) in pigs injected daily with rpST (1.98) compared with pigs of rhe conrrol group (1.65). Similar effects on weight gain, feed/gain ratio and cartilage lesion score have previously been observed by us (He et al 1994 (Table 1) are consistent with those reported previously (He et al 1994 (Nakano et al 1979), has been reported to be an important molecule involved in endochondral ossification, a process of long bone growth (Hunter 1991).…”
supporting
confidence: 82%
“…collagen undgti.oiurninoglycan concentrations in the weight-Fresh humeral condyles from both elbows were collected beari-ng u.eu-of .loint "u.iitug" (He et al 1994 …”
mentioning
confidence: 99%
See 1 more Smart Citation